Peran Ganda Media Sosial Dalam Kasus Kekerasan Seksual Anak: Antara Advokasi Publik dan Risiko Reviktimisasi Korban - Puannandini, Dewi Asri; Anggraeni, Devi; Octo Firmansyah Gulo, Deden; Ahmad Nur, Agum; Karabi, Jumadi K. (PT. Meja Ilmiah Publikasi, 2025)
Child sexual violence is a serious human rights violation with long-term consequences. In the digital era, social media plays a paradoxical dual role in handling these cases. This study aims to analyze the dual role of social media as a public advocacy tool that accelerates the legal process while simultaneously posing a risk of revictimization for child victims. Using a qualitative research method with normative legal and empirical approaches, this study examines legislation, content analysis of viral cases in Indonesia from 2020-2024, and in-depth interviews with child protection activists, legal experts, and law enforcement officials. The findings show that public pressure through social media has proven effective in accelerating law enforcement responses. However, at the same time, unethical exposure such as the dissemination of identities, negative comments, and stigma on digital platforms causes repeated trauma and profound psychological suffering for the victims. This situation is exacerbated by regulatory gaps that are not adaptive to the speed of social media and the low level of public digital literacy. In conclusion, justice that relies on virality is an unsustainable and dangerous system. A fundamental shift is required towards a collaborative approach involving the government, digital platforms, and the public to build a victim-centric digital ecosystem where the protection, recovery, and dignity of the child are the highest priority.